La idea de la ciencia y de la técnica moderna en el magisterio de Juan Pablo II (De 1978 a 1985) - Boccardo Rojas, Pedro (Veritas, 2005)
The author presents the ided that John Par I bas about science and modern technology; formulated in his various magisterial expressions since the begining of his Pontificate until the yeur 1985. The Hoy Father draws especial attention to the incidence of science and modern technology on human progres, as well as on their ambivalences and perils. The Pope's proposal si that science and modern technology should be at the service of culture and, therefore, at the service of man.